California Democratic Council Statewide Convention at Hacienda Inn - Watkins, Howard::::::::: (1982)
Keynote speaker U.S. Senator Ted Kennedy receiving standing ovation after speaking; shaking hands with Dan Whitehurst "Convention Banner: "We the people action for the '80's"